The impact of extensive medial frontal lobe damage on 'Theory of Mind' and cognition - Bird, C; Castelli, F; Malik, O; Frith, U; Husain, M (2004)
The ability of humans to predict and explain other people's behaviour by attributing to them independent mental states, such as desires and beliefs, is considered to be due to our ability to construct a 'Theory of Mind'. Recently, several neuroimaging studies have implicated the medial frontal lobes as playing a critical role in a dedicated 'mentalizing' or 'Theory of Mind' network in human brains. Here, we report a patient, G.T., who suffered an exceptionally rare form of stroke-bilateral anterior cerebral artery infarction, without rupture or the complications associated with anterior communicating artery aneurysms. Detailed high-resolution neuroanatomical investigations revealed extensive damage to the medial frontal lobes bilaterally, including regions identified to be critical for 'Theory of Mind' by functional neuroimaging of healthy human subjects. For the first time in such a patient, we carried out a thorough assessment of her cognitive profile including, critically, an experimental investigation of her performance on a range of tests of 'Theory of Mind'. G.T. had a dysexecutive syndrome characterized by impairments in planning and memory, as well as a tendency to confabulate. Importantly, however, she did not have any significant impairment on tasks probing her ability to construct a 'Theory of Mind', demonstrating that the extensive medial frontal regions destroyed by her stroke are not necessary for this function. These findings have important implications for the functional anatomy of 'Theory of Mind', as well as our understanding of medial frontal function. Possible reasons for the discrepancies between our results and neuroimaging studies are discussed. We conclude that our findings urge caution against using functional imaging as the sole method of establishing cognitive neuroanatomy.